2018
DOI: 10.4103/ijccm.ijccm_469_17
|View full text |Cite
|
Sign up to set email alerts
|

Study on clinical profile and predictors of mortality in Cerbera odollam poisoning

Abstract: Context:Cerbera odollam is a tree native to South Asia. It belongs to the poisonous Apocynaceae family. Deliberate self-harm with fruit of this plant is a major clinical problem in the developing world. Ingestion of C. odollam kernels is the cause of deaths in more than half of Kerala's plant poisoning deaths. The data on clinical features and complications of C. odollam poisoning are sparse, apart from a few case reports and limited studies.Aims:The present study was done to find the mode of presentation, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The body mass index of the consumer possibly determines the fatal amount [6]. In 102 patients studied by Renymol et al, consumption of more than two kernels was positively associated with mortality (OR of 5.12, CI of 1.54-17.04, and P = 0:004) [11]. Our patient with a BMI of 21.71 kg/m 2 reported consuming one seed and survived.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The body mass index of the consumer possibly determines the fatal amount [6]. In 102 patients studied by Renymol et al, consumption of more than two kernels was positively associated with mortality (OR of 5.12, CI of 1.54-17.04, and P = 0:004) [11]. Our patient with a BMI of 21.71 kg/m 2 reported consuming one seed and survived.…”
Section: Discussionmentioning
confidence: 56%
“…According to a 2016 study of 50 odollam poisoning cases in India, the most frequent symptom is vomiting (54% of the studied patients); thrombocytopenia was observed in 50% of patients; the most common ECG abnormality was sinus bradycardia (32%), followed by sinus pause (28%) [10]. However, another study out of India of 102 patients reported varying degrees of heart block (58%) as the most common ECG finding [11]. Junctional rhythm seen in our patient is infrequently reported [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations